FTIR: Important tool to investigate the chemical bond formation in the polycrystalline xBaTiO3 – (1-x)BiFeO3. (2021) - Shah, Manali N.; Patel, Nima H.; Shah, Devang D.; Mehta, P.K.
Abstract: In this work, polycrystalline fine powders of xBaTiO3 - (1-x) BiFeO3 (abbreviated in this article as xBTBF, where x = 0, 0.25, 0.5, 0.75 & 1.0; amount of concentration) has been synthesized by Solid State Reaction route (SSR) using extra pure carbonates and oxides. From the XRD analysis BTO and BFO exhibits pure phase structure without any kind of secondary phase while the structure of intermediate compounds has sustained the matrix of BTO and the unit cell of BFO is gradually merged in to BTO. Furthermore, the SEM results show that grains and grain boundaries are clearly visible with few amounts of defects. FTIR spectroscopy is used for estimation of bonds present in the samples. The broad nature of the absorption peak has been explained successfully in the view of distortions which are not evident through XRD. Depending on wave number various physical quantity like effective mass, bond length, frequency of vibration has been determined for Ti-O and Fe-O bonds. The obtained values of bond length have assured the formation of bond between Ti-O and Fe-O. The possibility of enhancement in electrical properties is also discussed in the light of obtained results.